ONLINE LEARNING ADOPTION DURING COVID19 PANDEMIC – THE EXPERIENCE OF THE UNDERGRADUATE STUDENTS IN NORTH MACEDONIA - Trenevska blagoeva, Kalina; Mijoska belshoska, Marina; Trpkova nestorovska, Marija (UNIVERSITY „St. KLIMENT OHRIDSKI “- BITOLA, FACULTY OF ECONOMICS – PRILEP, 2022)
Abstract Since spring 2020 when pandemic suddenly threatened the world in unexpected way, a dramatic shift in how people live, work, and learn/study is evident. Global pandemic restriction strategies like stay-at-home orders, social distancing and long periods of lockdowns have disrupted the traditional campus based model of education i.e. the traditional in-classroom teaching, and have forced fast adoption of online learning systems as remote/distance learning. For most counties/universities worldwide, online learning was one of the efforts to minimize the spread of Covid-19 and convenient opportunity of continuing the educational process in those circumstances. This was the case in the country as well. In this sense, the goal of this paper is to analyze the adoption of online learning among university students in the country. The basis for the research model is the original Technology Acceptance Model (TAM). This fundamental model examines the crucial predictors/factors of technology adoption including the following constructs: perceived ease of use, perceived usefulness, attitude towards using, behavioral intention and actual use. In order to get insights regarding the online learning adoption among university students in the country, a survey was conducted among more than 150 undergraduates during April and May 2022, while online learning was still undergoing. The results of this study capture valuable insights regarding the adoption of online learning and can be used as solid base for higher education institutions in the country to shape their online education offerings in order to remain competitive in a post-pandemic future. This research provides relevant practical implications by elaborating that the analyzed factors are critical towards online learning attitude in our country.
Keywords: Online Learning, Technology Acceptance Model, University Students, North Macedonia.